New species and new records of the genus Harpactea (Araneae, Dysderidae) from the Djurdjura National Park, Algeria - Chaib, Salma; Kherbouche-Abrous, Ourida; Beladjal, Lynda (Zootaxa, 2023)
Harpactea hamidae n.sp. is describe based on males from Tikjda region in the National Park of Djurdjura (Bouira, Algeria). It belongs to the species group and subgroup corticalis. Its distribution is summarized and discussed. New records for two other Harpactea species (H. heizerensis Bosmans & Beladjal, 1991 and H. innupta Beladjal & Bosmans, 1997) are presented.